Arrangements for the Termination of Investigations in the Prosecution of Criminal Cases of Domestic Violence According to Law Number 8 of 1981 Concerning the Criminal Procedure Law (Case Study of the East Dumai Police) - Dona Antonio; Risdalina Risdalina; Indra Kumala Sari M (Journal of Social Research, 2023)
Law No. 23 of 2004 concerning Domestic Violence in article 1 paragraph 1 states that the integrity and harmony of a happy, safe, peaceful and peaceful household is the dream of everyone in the household. This study aims to find out and analyze the arrangements for stopping investigations in the prosecution of criminal cases. As well as knowing and analyzing about knowing the process of stopping investigations in domestic violence criminal cases. This research belongs to the normative type of research. So it can be known that investigators as members of the Police, in principle, have discretionary authority. Termination of investigation is a discretionary policy of law enforcement with the requirement that if the perpetrator reneges on the peace agreement by repeating the violent crime, it will be directly processed formally (court). Based on the explanation above, it can be concluded that investigators as members of the Police, in principle, have discretionary authority.